ANALISIS ANALISIS KESALAHAN BERBAHASA DALAM PELAFALAN DAN DIKSI DI INTERAKSI PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS VII SMP AL-ISMAILIYAH: ANALISIS KESALAHAN BERBAHASA DALAM PELAFALAN DAN DIKSI DI INTERAKSI PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS VII SMP AL-ISMAILIYAH - Hawatib; Asri Bariqoh; Amirul Mukminin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2024)
Students' use of language still contains errors, including aspects of pronunciation (speech), diction (word choice), and sentence structure. One of the occurrences of language errors is that during discussion learning situations, students interact with non-standard language. Based on the description above, it is necessary to conduct research with the title Analysis of Language Errors in Pronunciation and Diction in Indonesian Language Learning Interactions in Class VII Al-Ismailiyah Middle School Students. The aim of this research is to describe the forms of pronunciation and diction errors in the Indonesian language learning process for Class VII students at Al-Ismailiyah Middle School. This research is qualitative research. There are three activities in data analysis, namely: 1. Data reduction 2. Data presentation 3. Drawing conclusions 4. Data collection. The results of the research showed that there were forty-five pronunciation errors in the Indonesian language learning process for class VII Al-Ismailiyah Middle School, which were caused by changes in phonemes. There were twenty errors in diction or word choice in the Indonesian language learning process for class VII Al-Ismailiyah Middle School which were caused by inappropriate word choice. Pronunciation errors are influenced by the use of regional dialects, namely regional languages ​​in communication, some of which originate from West Kalimantan where Malays live. Diction errors are also influenced by regional dialects that are often used, so that students become accustomed to them and prefer to use regional languages ​​that they have mastered first